PERSEPSI MASYARAKAT DESA SUNGAI AWAN KANAN TERHADAP KEBERADAAN HUTAN MANGROVE DI KAWASAN PANTAI AIR MATA PERMAI KABUPATEN KETAPANG - Kadhapi, Mu’ammar; Hardiansyah, Gusti; Zainal, Sofyan (JURNAL HUTAN LESTARI, 2015)
ABSTRACT Mangrove forest in the coastal area of Air Mata Permai is one source of the livelihood of local people. The relation between communities and the existence of mangrove forests has led to the perception of the communities as an effort to maintain and to conserve mangrove forests. This research objective is to look communities perception of the SAK Village to the presence of mangrove forests in the coastal area of Air Mata Permai district Ketapang and the factors that affect. The method used in this research is a survey method and technique of sampling or interviews with respondents conducted by purposive sampling. The number of respondents in this research is 90 respondents. The results showed the level of communities perception of SAK Village to the existence of mangrove forests in the coastal area Air Mata Permai tends to higher as many 52 respondents (57.78%) had a high perception, 25 (27.78%) of respondents have the perception medium and 13 respondents (14.44%) have a low perception. Keywords: Mangrove Forests, local communities, ccosystems and perception.